Investigating the effect of manipulatives on mathematics achievement: The role of concrete and virtual manipulatives for diverse achievement level groups - Ahmad, Sagheer; Siller, Hans-Stefan (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
This study investigates the impact of integrating both concrete and virtual manipulatives on the mathematics achievement of fifth-grade students across different achievement levels (low, average, and high). Utilizing a quasi-experimental design with pre- and post-tests, a convenience sample of fifth-grade students was randomly assigned to either a control or experimental group. The data collection instruments, consisting of separate pre- and post-tests on the same mathematical concepts, underwent thorough validity and reliability testing. Initial assessments demonstrated that the achievement levels between the control and experimental groups were comparable prior to the intervention. The experimental group received instruction that incorporated both concrete and virtual manipulatives, whereas the control group followed traditional teaching methods. Following a 12-week intervention period, a post-test was administered. The data were analyzed using parametric paired-sample t-tests and one-way ANCOVA, ensuring that all underlying assumptions were satisfied. The findings revealed significant improvements in post-test scores among students in the experimental group, regardless of their initial achievement levels. Although low-achieving students in the control group also showed progress, their gains were less substantial compared to those in the experimental group. This study highlights the potential benefits of incorporating both concrete and virtual manipulatives in fifth-grade mathematics instruction to enhance academic achievement.